Audit of peripartum hysterectomies at an Indian tertiary care centre: a 12-year review - Sandhya Gadre,; Chaudhary, Gunjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Peripartum hysterectomy is performed in critical conditions like major obstetric haemorrhage, abnormally-invasive placenta, rupture uterus. In developing countries incidence is 0.2–5/1000 deliveries. It can also be done as non-emergent surgeries for suspected cases by pre-planning. If high-risk patients are identified, timely intervention done, yields better outcome. Data of peripartum hysterectomy patients during last 12 years collected. Demographic details, menstrual-obstetric history, high-risk factors, previous and current delivery details, postpartum haemorrhage, indication, operative details of peripartum-hysterectomy, maternal-perinatal outcome, blood loss, anaesthesia records, length of ICU and hospital stay quantity of blood and products transfused analysed. 18 cases of peripartum hysterectomy with incidence of 2.76 per 1000 deliveries noted. 14-emergency, 4-electively done. In current pregnancy 13 had caesarean deliveries, 5 had vaginal deliveries, all required emergency hysterectomy. Majority were 26-30 years, 83% multiparous. 11 required emergency hysterectomy. 27.77% were due to atonic PPH and 22.22% placenta accreta spectrum. Mean anaesthesia duration, ICU stay, mean blood loss, units of blood and products was more in emergency group. Maternal and perinatal outcomes were favourable in elective group. Keeping high index of suspicion for accrete, identifying risk factors for atonic PPH, managing proactively, results in favourable maternal-perinatal outcome.